Effect of non-conventional chemicals on susceptibility of rice seedlings to blast disease - and J.C. DAS, DAISY SENAPOTY1*, K.N. BHAGABATI2 (Indian Phytopathology, 2002)
Twenty-one non-conventional chemicals were tested against blast disease of rice caused by Pyricularia grisea [Magnaporthe grisea]. Results revealed that cadmium chloride (10-4 M), ferric chloride (10-4 M), lithium sulfate (10-3 M), magnesium sulfate(10-3 M), potassium chloride (10-3 M), sodium fluoride (10-3 M), sodium molybdate (10-4 M), sodium silicate (10-4 M) and zinc sulfate (10-4 M) could control the disease effectively. When tested by the ’poison food technique’, these chemicals showed no in vitro fungitoxicity at their effective concentrations.